Lessons Learned from the COVID-19 Pandemic for Pediatric Workplaces. Issue 5 (September 2020) - Beal, Judy A.
Abstract : The COVID-19 pandemic has shown the best of the best in nursing. Nurses are using scientific evidence to guide care, leading teams of clinicians into uncharted territory, and supporting patients, families and co-workers at unprecedented levels. Our pediatric nursing expert, Dr. Beal, highlights lessons to be learned that can strengthen the quality of pediatric work environments.